Cisplatin for testicular germ cell tumors: a rapid review. Issue 3 (August 2016) - Hu, Zhiqiang; Yu, Jiajie; Gui, Ge; Chen, Yuan; Huang, Rui; Jiang, Lucan; Kwong, Joey S.W.; Li, Youping; Zhang, Lingli
Abstract: Objective: Cisplatin is one of efficacious medicines for TGCT, but is not in 18 th WHO EML now. The Union for International Cancer Control recommended cisplatin to the 19 th WHO EML for TGCT. To evaluate the effectiveness, safety and cost of cisplatin for TGCT according to the requirements of WHO EML Expert Committee, and to provide the evidence whether cisplatin should be included in WHO EML. Method: We searched The Cochrane Library, PubMed, EMbase, NHS EED, US National Guideline Clearinghouse (NGC) and WHO guidelines. Guidelines and systematic reviews (SRs) on cisplatin for TGCT were included. Two reviewers selected studies and extracted relevant information independently. Quality of SRs was appraised through AMSTAR. Results: Seven guidelines and four SRs were included in this rapid review. Quality of SRs was moderate according to AMSTAR. The results showed that: (a) effectiveness: cisplatin‐based chemotherapy significantly improved in response rates and overall survival for more advanced disease (stage II and stage III). Bleomycin, etoposide, and cisplatin (BEP)—one of the most widely used of cisplatin‐based chemotherapy regimens should be considered as the standard treatment of good‐prognosis patients with survival rates of 90% and as the best option for intermediate‐ or poor‐prognosis patients with survival rates of 75% and 50%, respectively. (b) Safety: nephrotoxicity, ototoxicity and peripheral neuropathy are common adverse effects of cisplatin. (c) Cost: there was no relevant study about cost of cisplatin for TGCT. But the affordability of cispaltin is good for Chinese patients, due to it is in health insurance directory of China. Conclusions: We recommend cisplatin to be listed in 19 th WHO EML for TGCT, due to adequate evidence of effectiveness and good affordability.